Cash Flow, Profitability, Financial Constraint, and Investment in Indonesia - Risal Rinofah (Universitas Sebelas Maret, 2016)
This study aims to find the effect of cash flow, profitability, and financial constraint on investment decision in Indonesia. Previousstudies have proved that cash flow, profitability, and financial constraint have an effect on company investment level. The utilization of logit regression model to classify the condition of financial constraint and multiple regression on the 123 samples of manufacturing companies during 2012 – 2014 period find that cash flow and profitability has a positive effect on investment level in company that face financial constraint and financial unconstraint company. The moderating test shows that profitability has stronger effect on the investment level that experience financial constraint rather than in financial unconstraint company. Meanwhile, cash flow does not have different effect on financial constraint or unconstraint companies.